Estimating a fiscal reaction function for the South East European countries - Tashevska, Biljana; Trpkova nestorovska, Marija; Trenovski, Borce (Croatian Statistical Association, 2018)
The global economic crisis caused a deterioration in the public finances of the South East European countries. Hence, the fiscal sustainability issue became important not only for developed EU countries (considering the European debt crisis), but also for the SEE region. The paper analyses how primary government balances in South East Europe adjust to increasing government debt and to the economic cycle, by estimating a panel fiscal reaction function. The main goal is to test whether fiscal policy tends to react to a sufficient extent to increasing public debt in order to ensure long-term fiscal sustainability. The empirical results imply a pro-cyclical fiscal policy in the SEE countries. The results also show an initial deterioration of the primary balance after a rise in the debt level, which is not consistent with sustainability of public finances. However, in the medium run primary balance seems to adjust to rising debt.
Keywords: fiscal reaction function, fiscal sustainability, South East European countries